Density functional calculation for electronic structure properties of graphene adsorbed with GaAs nanostructure - Abubakar, Shamsu (2014)
Graphene and GaAs nanostructures are well-known materials that have potential application in modern high-speed electronic devices, due to high electron mobility which makes their properties desirable. Until now, the adsorption mechanism of GaAs nanostructure on graphene with a view to change its electronic structure properties has yet to be understood. For that reason, this study is conducted on altering the electronic structure properties of graphene, as semi-metallic material using GaAs nanostructures. This semi-metallic nature needs to be overcome before graphene can be proposed as a metal-substrate for nanoscale growth. In this work, density functional calculation employed is based on quantum mechanical method, used to examine the possible effect of small number of adsorbed Ga and As adatoms as well as their dimer on graphene. This calculation is performed using exchange-correction functional to obtain the structural stabilities and electronic properties of graphene adsorbed with GaAs nanostructure. A simplifying approach of k-points sampling and pseudopotentials approximation are also used in the calculation. The computational software package used based on density functional theory for this calculation is QUANTUM ESPRESSO. The results of the calculation have indicated that the convergences with respect to plane-wave energy cutoff and with k-points sampling grids have been achieved. This calculation is performed in order to determine the stable height between the Ga and As adatoms on graphene and subsequently, the most stable adsorption sites of the individual atoms and dimer on graphene are obtained. After optimization, the lattice constant for a pristine graphene, a = 2.46 Å is in agreements with the experimental value found in literatures. For the calculated adsorption site of Ga adatom on graphene, H-site is found to be energetically stable. The bond distance between gallium adatom and the neighboring carbon atoms in the graphene structure on H-site is 2.26Å, which is in closer agreement with the value of 2.20Å, found in other previous study. In the case of arsenic adatom on graphene, B-site is the most stable adsorption site and the electronic structure of graphene is affected significantly, as a result of the charge transfer and weak hybridization. The magnetic moment for gallium and arsenic adatoms as well as their dimer is found to be 0.00, which signify the non-magnetic behavior in graphene that is adsorbed with GaAs nanostructure. It has also been found that the orbital contributions for C-GaAs bond are mainly dominated by pz orbitals of carbon and px and py orbitals of GaAs. This study has significantly found that the semi-metallic behavior in graphene is changed to metallic as a result of orbitals-hybridization with GaAs nanostructure. Therefore, these new features make graphene a wonderful material for potential uses in electronic device and also as prepared substrate, used for the epitaxial growth of nanowires.